Enhancement of proton conductivity of polymer electrolyte membrane enabled by sulfonated nanotubes - Zhang, H.; Ma, C.; Wang, J.; Wang, X.; Bai, H.; Liu, Jian (Elsevier Ltd, 2014)
Proton exchange membrane (PEM) with high proton conductivity is crucial to the commercial application of PEM fuel cell. Herein, sulfonated halloysite nanotubes (SHNTs) with tunable sulfonic acid group loading were synthesized and incorporated into sulfonated poly(ether ether ketone) (SPEEK) matrix to prepare nanocomposite membranes. Physicochemical characterization suggests that the well-dispersed SHNTs enhance the thermal and mechanical stabilities of nanocomposite membranes. The results of water uptake, ionic exchange capacity, and proton conductivity corroborate that the embedded SHNTs interconnect the ionic channels in SPEEK matrix and donate more continuous ionic networks. These networks then serve as proton pathways and allow efficient proton transfer with low resistance, affording enhanced proton conductivity. Particularly, incorporating 10% SHNTs affords the membrane a 61% increase in conductivity from 0.0152 to 0.0245 S cm-1. This study may provide new insights into the structure-properties relationships of nanotube-embedded conducting membranes for PEM fuel cell. Copyright © 2013, Hydrogen Energy Publications, LLC.